Healthy Baby Delivery of a COVID-19 Infected Mother in Iran: Process and Protection - Lotfollah Davoodi; Hamidreza Samaei; Hamideh Abbaspour Kasgary; Parisa Moradimajd (Mazandaran University of Medical Sciences, 2021)
Background: In late December 2019, a kind of pneumonia caused by a novel coronavirus (SARS-CoV-2) emerged in Wuhan, Hubei Province, China. This virus rapidly spread worldwide and infected 195 countries and territories, including Iran. By March 22, 2020, the virus had affected more than 40000 people worldwide and caused more than 19000 deaths. Pregnant women are a vulnerable group to viral infections because partial immune suppression occurs during pregnancy. Therefore, the COVID-19 epidemic may cause a rising global concern about its consequences for pregnant women and fetuses. Objectives: In this case study, we report the delivery of a pregnant woman after her COVID-19 confirmation. Methods: We report a 44-year-old pregnant woman (32 weeks gestation) with COVID-19 who gave birth to a healthy baby with no evidence of COVID-19. We did not observe any worse clinical outcomes, such as maternal mortality, stillbirth, spontaneous abortion, and preterm delivery. Results: A preterm baby girl with 2500 g weight and Apgar scores at 5 minutes and 10 minutes were 9 and 10 was delivered. The preterm baby was normocephalic, had no icteric sclera, and the heart sounded normal without murmurs, Lung ventilation was normal. Conclusion: Viral pneumonia may severely be presented in pregnancy because of physiological and immunological changes and shift from cell-mediated to humoral-mediated immunity during the pregnancy period. Vertical transmission of COVID-19 from mother to child, short-term and long-term adverse effects on mother and newborn are still unclear and controversial.